Exclusão digital de gênero na arquivística: a produção de um modelo de pesquisa que permita identificar o fenômeno - SOARES, Elieth das Chagas (2017)
Information technology drives the dissemination of information and the capacity for data processing, but it entails the strengthening of the pre-existing model of gender identification in the western patriarchal society. This phenomenon has been named as "Digital Gender Exclusion" (DGE), that is, the inability or impossibility of women to master and take advantage of computer technology. The objective of this work is to make a brief state of the art about the DGE and to propose categories and questions that allow to identify evidences of it, in a formative space like that of Faculty of Archivingof the UFPA (FAARQ). For this, the factors that indicate the presence of DGE according to the literature of the area should be analyzed, with the aim of creating a research instrument that allows identifying the phenomenon. The construction will serve as the basis for a pilot test that will try to verify possible differences in the field of Information Technology among the students of Archiving, due to their gender characteristics. As a methodology, a literature review was done with the aid of specific descriptors, investigated in national databases. We selected articles on the digital gender exclusion pertinent to the theorization about DGE, and the factors that characterize it. After the selection of the material, a small state of the art on the EDG was made to identify the factors that can reveal this phenomenon and thus, to base an instrument of identification of the DGE. The final result of the research makes a proposal of factors that could base an instrument to detect the DGE, contributing to the development of research on this subject in the community of Archiving and other professionals of the information. Next step should be the complementation and implementation of this proposal in a pilot survey, to be applied in the population of the Faculty of Archiving, to verify the existence and dimension of this phenomenon in the training of archivists.